Evaluating adaptive hypotheses for female-led infanticide in wild chimpanzees. (October 2021) - Walker, Kara K.; Foerster, Steffen; Murray, Carson M.; Mjungu, Deus; Pusey, Anne E.
Abstract : Although rare among group-living primates, infanticide by females has been reported in several chimpanzee, Pan troglodytes, populations. We examined 13 infanticidal attacks over 47 years at Gombe National Park, Tanzania to evaluate three adaptive hypotheses. (1) Exploitation of the infant as a food resource – by eating a vulnerable neonate, attackers gain calories that may be important during periods of food scarcity or energetic stress. (2) Resource competition – Gombe females concentrate their foraging in overlapping core areas and dominance rank influences foraging success. By killing the infant of a female with high core area overlap, the perpetrator removes a current and future competitor, improving her access to food. (3) Low cost – female chimpanzees mature and reproduce slowly, and longevity increases reproductive success. Physical aggression causes risk of severe injury or death, so females will only mount attacks when risks to the perpetrator are low. In support of hypothesis 1, females usually consumed the carcass. However, attacks were not more likely in times of resource or energy scarcity. In support of hypothesis 2, females attacked others with whom they shared core areas, but attacks did not cause shifts in ranging patterns. In support of hypothesis 3, one or more attackers always outranked the victim, the attacks often involved coalitions and victims usually lacked kin support. Attacks were more likely to be successful when attackers were not hindered by clinging infants and victims could not retreat. Our results provide further evidence for female competition and the adaptive value of female-led infanticide in this species. Highlights: We documented 13 female-led infanticidal attacks in one chimpanzee community. Infant victims were usually eaten, providing immediate nutrition to the attacker. Attackers targeted likely competitors whose foraging areas overlapped their own. Attackers usually targeted neonates of lower-ranking mothers who lacked kin support.